Malaysia - Stads, Gert-Jan; Ali, Roslina Binti; Omot, Norah; Nin-Pratt, Alejandro; Nguyen, Pham Thi (International Food Policy Research Institute, 2020)
Malaysia’s total agricultural research spending remained stagnant in the decade leading to 2017, averaging around 0.9 to 1.0 billion ringgit per year (in constant 2011 prices).